2006
DOI: 10.1175/jcli3826.1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sea Surface Temperatures on the Northern Winter Stratosphere: Ensemble Simulations with the MAECHAM5 Model

Abstract: The role of interannual variations in sea surface temperatures (SSTs) on the Northern Hemisphere winter polar stratospheric circulation is addressed by means of an ensemble of nine simulations performed with the middle atmosphere configuration of the ECHAM5 model forced with observed SSTs during the 20-yr period from 1980 to 1999. Results are compared to the 40-yr ECMWF Re-Analysis (ERA-40). Three aspects have been considered: the influence of the interannual SST variations on the climatological mean state, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

61
438
5
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(505 citation statements)
references
References 43 publications
61
438
5
1
Order By: Relevance
“…The pioneer modeling works of Sassi et al (2004) and Manzini et al (2006) showed a negligible response to La Nina in the polar stratosphere, which was not statistically different from neutral winters. Nonetheless, more recent modeling studies reported a significant stratospheric cooling during La Nina (Calvo et al 2010) and a robust strong vortex related to suppressed anomalous upward propagation (Li and Lau 2013).…”
Section: Summary and Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The pioneer modeling works of Sassi et al (2004) and Manzini et al (2006) showed a negligible response to La Nina in the polar stratosphere, which was not statistically different from neutral winters. Nonetheless, more recent modeling studies reported a significant stratospheric cooling during La Nina (Calvo et al 2010) and a robust strong vortex related to suppressed anomalous upward propagation (Li and Lau 2013).…”
Section: Summary and Discussionmentioning
confidence: 85%
“…Several indices have been used in the literature, considering different oceanic regions, such as Nino-3 (N3) (5°N-5°S, 150°-90°W) (Hoerlinget al 1997;Manzini et al 2006) or Nino-4 (N4) (5°N-5°S, 160°E-150°W) (Kug and Ham 2011;Zhang et al 2015). However, most recent studies used the Nino-3.4 (N3.4) (5°N-5°S, 170°-120°W) index from the National Centers for Environmental Prediction/Climate Prediction Center (NCEP/CPC) (e.g., Free and Seidel 2009;Butler and Polvani 2011;Garfinkel et al 2012;Butler et al 2014;Barriopedro and Calvo 2014;Domeisen et al 2015).…”
Section: A Event Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manzini et al, 2006;Orsolini et al, 2008, and references therein), it is surprising that the PNA impact on the coldness of the polar stratosphere is not as important as the one exerted by the West-Pacific pattern. This may arise from the fact that the PNA pattern is associated with flux anomalies that are not located as poleward, nor extending as high into the stratosphere as the West-Pacific pattern (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…However, most climate model simulations are performed by prescribing globally uniform SST increases (e.g., Shu et al, 2011), and the impacts of SST gradient changes on stratospheric circulation and temperatures are rarely discussed. Both modeling and observational studies have shown that the SST changes associated with ENSO events have significant effects not only on tropospheric circulation (e.g., Seager et al, 2003;Feng et al, 2013) but also on stratospheric circulation (e.g., Manzini et al, 2006;Xie et al, 2011Xie et al, , 2012. The BDC, for instance, is strengthened during warm phases of ENSO events via enhancement of the vertical propagation of waves (e.g., Sassi et al, 2004;Calvo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%